Assessment of Heart Rate Variability in Fibromyalgia after Micro-physiotherapy. - Pereira, Adriano Pinto; Carvalho, Eluciene Maria dos Santos; Kerppers, Ivo Ilvan; Furmann, Meiriélly; Pires, Juliana Aparecida Wosch; Ribeiro, Larissa Gulogurski; Rolão, Marcos Paulo Polowei; Salgado, Afonso Shiguemi Inoue (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Fibromyalgia syndrome is characterized by musculo-skeletal pain. Heart rate variability (HRV) is a versatile and promising non-invasive marker of the autonomous nervous system. Micro-physiotherapy involves manual physiotherapy that seeks to identify the primary cause of a disease or symptom and to stimulate self-healing, in which the body recognizes the aggressor (antigen) and begins the elimination process, through cellular and tissue reprogramming. Method: The sample was composed by 15 individuals, aged between 35 and 40 years, with fibromyalgia. The Nerve Express method was used to assess the variability of the heart rate. Two sessions of micro-physiotherapy were conducted using global methods, with an interval of 45 days between sessions. Results: Based on the HRV results, the high frequency band was confirmed at p=0.203, with the low frequency recording a statistically significant value of p=0.001, thereby demonstrating sympathetic activity. Upon comparison of the mean heartbeat before and after treatment, a value of p=0.0006 was obtained. A value of p=0.049 was recorded in the analysis of the median R-R interval values. Conclusion: The use of micro-physiotherapy as a treatment method for fibromyalgia effectively improved the lives of patients by promoting sympathicotonia.